Estudo da Influência do Sm e Er em Cerâmicas de PbTiO3 - Paris, Elaine Cristina (2005)
In this work, it was obtained powders and thin films of (Pb1-xLnx)TiO3, Ln = Sm and Er, using a chemical method of synthesis, polymeric precursor method (Pechini). In this way, the synthesis conditions were optimized in order to minimize the formation of secondary phases. (Pb1-xSmx)TiO3, PST and (Pb1-xErx)TiO3, PET powders, with x varying from 0.01 to 0.1, were obtained in pH 7 and calcined at 600°C for 2 and 8 hours in oxygen atmosphere. There was not formation of secondary phase (pyrochlore) up to 4 mol% of Sm. On the other hand, the solubility limit was already reached at the PbTiO3 (PT) lattice, when doped with 4 mol% of Er. The increase of the percentage of dopants favors the beginning of the tetragonal to cubic phase transition. In this transition, up to 2 mol% of dopants, Er is more efficient than Sm and for above that, an inversion of this behavior occurs. It was observed by micro-Raman spectroscopy and DSC that the addition of Sm or Er to the PT causes a decrease of Curie temperature of the material in relation to the pure PT (~ 490°C). PST and PET thin films were obtained by spin coating on Pt/Ti/SiO2/Si substrate and heat treated at 600°C for 2 hours for the crystallization of the films. It was observed for both PST and PET films are occurring the beginning of the tetragonal to cubic phase transition, resulting in PT with low tetragonality, with the increase of the dopants concentration. It was also verified that these films are textured in the (001) and (100) family plans with both dopants, being a axis direction favored. The obtained films presented nanometric grain sizes and the addition of dopants (Sm or Er) in the PT lattice resulted in a decrease of the average grain size. In order to improving the dielectric and ferroelectric properties of the PST and PET films, it was varied: Sm or Er concentration, number of layers, viscosity of the precursor solution, deposition speed, heat treatment, the bottom electrode and the organic precursor concentration. In the results of electric measurements, it was verified that the Er addition is more efficient than Sm in the increase of the dielectric constant and improvement of ferroelectric properties of the films. It was also observed that the decrease of the tetragonality of the films, with the consequent beginning of the tetragonal to cubic phase transition of the material, there is a reduction of the dielectric constant values and of the remanent polarization for the samples. Using the LaNiO3 like bottom electrode in substitution to the Pt, it was obtained approximated values of dielectric constant, however this substitution resulted in better ferroelectric properties of the films. In spite of obtaining smaller dielectric constant values than those found in the literature, it could be observed that the decrease of the concentration of organic precursors improved the electric properties of the PST and PET films, indicating a dependence relationship of the amount of organic material present in the precursor solution in function of obtaining thin films with satisfactory dielectric and ferroelectric properties.